1982
DOI: 10.1017/s0047404500009039
|View full text |Cite
|
Sign up to set email alerts
|

What no bedtime story means: Narrative skills at home and school

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Cambridge University Press is collaborating with JSTOR to digitize, preserve and extend access to Language in Society.http://www.jstor.org In a series of "reading cycles," mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
0
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 977 publications
(230 citation statements)
references
References 12 publications
2
165
0
11
Order By: Relevance
“…Routines in CLE programming imitated parent-child language development interaction of the kind described by Bruner (1983Bruner ( , 1986) and other researchers in child language development that were emerging at the time (Goldfield & Snow, 1984;Heath, 1982Heath, , 1983Nineo & Bruner, 1978;Snow, 1977Snow, , 1978Snow, , 1983aSnow, , 1983bSnow & Goldfield, 1982Wood, 1980;Wood, Bruner, & Ross, 1976). In a routine, the same text was revisited repeatedly over time and both the scope of the context for the text production and the language resources used within the text itself were expanded and developed qualitatively.…”
Section: Original Cle Research Implication In Australiamentioning
confidence: 94%
“…Routines in CLE programming imitated parent-child language development interaction of the kind described by Bruner (1983Bruner ( , 1986) and other researchers in child language development that were emerging at the time (Goldfield & Snow, 1984;Heath, 1982Heath, , 1983Nineo & Bruner, 1978;Snow, 1977Snow, , 1978Snow, , 1983aSnow, , 1983bSnow & Goldfield, 1982Wood, 1980;Wood, Bruner, & Ross, 1976). In a routine, the same text was revisited repeatedly over time and both the scope of the context for the text production and the language resources used within the text itself were expanded and developed qualitatively.…”
Section: Original Cle Research Implication In Australiamentioning
confidence: 94%
“…Second, it must be acknowledged that examining narrative abilities in only one language may not portray the full extent of bilingual children's narrative abilities. Third, it is important to keep in mind that there may be variation in the home literacy practices that exist within different Spanish dialect groups (Harwood, Leyendecker, Carlson, Asencio, & Miller, 2002;L. Reese et al, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Parent-child interactions (e.g., talk, shared reading), adult modelling of literacy behaviours, parental attitudes about literacy practices, and available resources (e.g., number of books in the home) have been found to be significantly associated with literacy skills of children (e.g., Baker et al, 1997;Beals et al, 1994;Collins and Michaels, 1980;Dickinson and Tabors, 2001;Hart and Risley, 1995;Lonigan, 2004;Heath, 1982;Huttenlocher et al, 2002;Miller and Moore, 1989;Phillips and Lonigan, 2005;Scarborough and Dobrich, 1994;Weizman and Snow, 2001;Whitehurst and Lonigan, 1998). For example, when Payne et al (1994) studied the language ability of young American children and their caregivers, they found that a composite home-literacy measure (composed of the following: the frequency and duration of talk; frequency of shared book reading; reports of child's independent exploration of text; visits to the library; the time the caregiver spent reading alone; the number of books in the home) was strongly associated with child language skills (word knowledge, story telling, etc.).…”
Section: Print-related Practicesmentioning
confidence: 99%
“…The quality and amount of talk between caregivers and young children has been found to have a significant effect on language use and literacy development (Beals, 2001;Beals et al, 1994;Collins and Michaels, 1980;Davidson and Snow, 1995;DeTemple and Beals, 1991;Dickinson and Tabors, 2001;Dunn and Dunn, 1981;Hart and Risley, 1995;Hoff and Naigles, 2002;Huttenlocher et al, 2002;Dickinson and Tabors, 2001;Weizman and Snow, 2001), and may be related to within-culture differences in language tradition (e.g., Collins and Micheals, 1980;Heath, 1982). For example, Weizman and Snow (2001) found that the number of words in adult talk in adult-child dyads was positively associated with child vocabulary production and that the most sophisticated levels of talk (in terms of the vocabulary used) occurred during shared book reading, which has also been found to be a significant predictor of reading performance (e.g., Hart and Risley, 1995;Sénéchal and LeFevre, 2002).…”
Section: Oral Practicesmentioning
confidence: 99%
See 1 more Smart Citation